PENGARUH DISIPLIN BELAJAR TERHADAP MOTIVASI BERPRESTASI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Agus Fadrian (LP3M | STKIP YPM Bangko, 2022)
Achievement motivation is a factor in determining student learning outcomes. Based on the initial survey of the achievement motivation of the students of the Faculty of Economics, Padang State University, it is still not as expected. These symptoms are closely related to learning discipline. This study aims to find out empirically how much influence learning discipline has on achievement motivation. This study uses a quantitative method by using the regression method and taking samples using the Stratified Propotinal Random Sampling technique. The instrument used is a questionnaire with a literal scale that has been tested for validity and reliability. Data were analyzed using SPSS computer program. The results of data analysis show that there is a significant influence of learning discipline on achievement motivation of students of the Faculty of Economics, Padang State University